The phase of love in the lyrics of the song “di timur” by Sal Priadi (Semiotic analysis) - Choirunnisa', Amellia; Alfian Setya Nugraha (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this research is to examine and interpret the lyrics of a song entitled